ANALYSIS OF INDONESIAN LANGUAGE ERRORS ON THE INDO TIMES NEWS SITE IN THE AUGUST 2023 EDITION EDUCATION CATEGORY BASED ON LINGUISTIC CATEGORY (PHONOLOGY AND MORPHOLOGY) - Pani Aulia Rukmana; Silfa Milatul Istiqomah; Risya Mitha Canestry; Nela Yunita; Ai Siti Nurjamilah (Media Inovasi Pendidikan dan Publikasi, 2023)
Language errors are an event that is inherent in every use of language, both orally and in writing. Both adults who have mastered the language, children, and foreigners who are learning a language can make language errors when they use the language. Based on the problem in the problem formulation, it is necessary to formulate a clear goal as a basis for analyzing language errors. . The aim of this analysis is to describe, correct and analyze forms of language errors on the August 2023 edition of the Indo Times news site in the education category based on linguistic categories (phonology and morphology) to determine the frequency of language errors in this situation in order to further develop and develop language skills. The method used is descriptive qualitative. The results of this research show that of the 28 news texts with 6 news texts used as samples, there are 17 errors, including52,94% errors at the phonological level and 47,06% errors at the morphological level.